QOLP-26. ANALYSIS OF REDDIT USERS' PERSPECTIVES OF BRAIN TUMORS. (12th November 2021) - Tripathi, Sanidhya; Prabhu, Arpan; Thomas, Kevin; Parker, Pearman; Rodriguez, Analiz
Abstract: BACKGROUND: Reddit, ranking 6 th in worldwide Internet site traffic, is a commonly used forum among patients and caregivers affected by brain tumors to discuss diagnoses, treatment, and self-care management. The use of the online forum may suggest patients and caregivers have unmet needs and are seeking further support outside of the clinical setting. We aimed to examine trends from Reddit discussion treads on brain tumors to identify areas of need in patient care. METHODS: We used a qualitative, descriptive design to understand patient and caregivers unmet and met needs. We analyzed the top 100 posts and accompanying 271 comments from the 'braincancer' subreddit to identify common themes. RESULTS: The qualitative content analysis revealed three major topic areas: (1) moving through the grief process; (2) processing diagnostic pathway; and (3) expressing gratitude toward other Reddit users. Most of the authors of the posts were patients with brain tumors ( n = 32; 38.5%) who used Reddit as a reflective journaling tool to move through the grief process for themselves or loved ones. About 47% of theses posts discussed the diagnostic process of glioblastoma multiforme (GBM) brain tumors, where users requested an inclusive/welcoming environment in the clinic by their healthcare professionals (HPs). Users also solicited and gave support for other members in the online community. CONCLUSIONS: This study highlights the need of implementing social media as a part of HPs' repertoire for patient outreach/needs. Furthermore, social media outlets like Reddit can help HPs understand the level of support they can give to their patients. Plans of action for physicians seeking to meet the needs of brain tumor patients include monitoring the concerns of patients, becoming verified on the platform/openly identifying themselves online, or conducting 'Ask Me Anything' discussions to educate patients.